Model pembelajaran connectivism untuk meningkatkan pemecahan masalah keterampilan belajar siswa di MTs. Nurul Jadid Kota Mojokerto - mustain, mustain (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2016)
Connectivism learning model to improve students' problem solving skills are intended to provide teaching materials that match the characteristics of the students. The focus in this study a Connectivism learning products to enhance problem-solving skills for students at MTs. Nurul Jadid Mojokerto. Connectivism learning products to enhance problem-solving skills for students at MTs. Nurul Jadid Mojokerto has been refined based on the analysis of trial data. Based on the measures that have been implemented can be concluded as follows. 1). Products developed interesting for classical learning in the classroom and independently. 2) The products of this product can ease the burden of teachers in teaching. 3) The results of expert validation and testing, it's a good learning model connectivism used for subjects.4) Judging the results of analysis of the quality of the learning model connectivism above it can be concluded that the RPP / Scenario Learning is already fit for use for the trial because the score of each component which is an indicator for the learning model connectivism no less than 3.0. 5) The results of the questionnaire data processing model of learning by using learning connectivism known that the average student's choice is 3:53, it is considered Enough with standard deviations 12:35